A comprehensive review on lignin pyrolysis: Mechanism, modeling and the effects of inherent metals in biomass. (1st February 2022) - Leng, Erwei; Guo, Yilin; Chen, Jingwei; Liu, Shuai; E, Jiaqiang; Xue, Yuan
Highlights: Effects of critical factors on lignin pyrolysis are summarized. Estimated energies by different DFT methods for the initial reactions are compared. Effects of different inherent metals with different existing forms are summarized. Kinetic modeling is discussed on structure representation and reaction network. Recommendations are suggested for experimental and simulation research on lignin pyrolysis. Abstract: This work comprehensively reviews the pyrolysis of lignin from the aspects of mechanism, modeling, and effects of inorganic species. Initially, the lignin general pyrolysis characteristics are described in detail. The effect of lignin isolation methods on pyrolysis characteristics and product distribution, together with the interactions between the lignin and holocellulose are considered. Then, the depolymerization mechanism of lignin, i.e. homolytic reaction and concerted decomposition, as well as the conversion mechanism of propionic acid side-chain and oxygen-containing functional groups in monomers, aree discussed. Moreover, three main types of zero-dimension models of lignin pyrolysis, viz. lumped kinetic models, network models, and mechanistic models are reviewed with the special attention paid to the structure representation and reaction network. Influences of alkali metals, alkaline earth metals, and transition metals on the lignin pyrolysis are concluded from four aspects, including metal-catalyzed lignin pyrolysis experiments, metal minerals migration and transformation, quantum chemical simulation calculations, and the modeling. Finally, challenges and prospects are discussed in the last section of this article.